LAYANAN RUMAH SAKIT BERBASIS RELIGI: SUATU KONSEPTUAL MODEL - Murjito, Winarno Heru; Kuntaryanto, Oki; Hartati, Nuraeni; Hartanto, Hartanto; Setyawanti, Dandang; Uningowati, Dwi Wahyu; Yuwono, Suhud Eko (Widya Dharma Journal of Business - WIJoB, 2024)
This study aims to develop a conceptual model to determine the competitive advantages of each religious-based hospital in Klaten Regency in order to establish appropriate marketing strategies to satisfy and increase public interest in trusting the quality of services provided by the hospitals. The novelty of the research lies in integrating the concepts of competitive advantage and performance quality of religious-based healthcare institutions through positioning mapping using multidimensional scaling models. In the final stage of the research, it is expected to form a positioning map for each religious-based hospital, thus creating competitiveness among each leading hospital in Klaten Regency in anticipation of achieving the Sustainable Development Goals (SDGs) and attaining optimal sharia economic growth in the healthcare sector by 2045